Planning for Handling COVID-19: Qualitative Study of COVID-19 at Sukorejo Community Health Center - Trisnindasari, Aisyah Lely; Rasni, Hanny; Susanto, Tantut (Jurnal Kesehatan Komunitas Indonesia, 2024)
Background: Health workers at Community Health Centers have an important role as the main guard in preventive and promotive efforts during the COVID-19 pandemic. Purpose: The aim of this research is to analyze the existence of planning for handling COVID-19 at the Sukorejo Jember Community Health Center in accordance with the first pillar in the WHO standards for planning for COVID-19. Methods: This research uses a descriptive phenomenological approach aimed at health workers involved in planning the handling of COVID-19 at community health centers. Data has been saturated in 3 health workers. Researchers analyzed the data using Collaizi analysis. Results: The results of the research have obtained three important themes, including team planning (human resources) in dealing with COVID-19, logistical needs, and preparation of activity implementation plans. Conclusion: Therefore, planning for handling COVID-19 is important in identifying and evaluating appropriate planning in infectious disease eradication programs at Community Health Centers.   Keywords: COVID-19, planning, health care provider, public health center